Mysticism Reloaded (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
The critical turn in religious studies proved an invaluable, contextual corrective to naïve essentializations of the category of mysticism. However, over the past few decades, this left comparative mysticism studies in a state of turmoil. Now, researchers are finding that this added sensitivity does not require abandoning the term altogether, and that we must somehow account for the self-evident similarity and spread of practices and phenomena that may be loosely grouped under the family-resemblance term of “mysticism.” Indeed, a post-critique recovery of mysticisms appears to be underway in multiple disciplines and settings. This Reprint developed as a Special Issue from this post-critique impulse to probe new approaches, methods, and theories to study mysticisms. It invited theoretical, methodological, and empirical research papers from any disciplinary perspective to shed new light on how to study mysticism in any religious or non-religious context. The papers may be used as independent, disciplinary references but also collectively by comparative mysticism scholars and advanced students. Contributions to the Reprint all relate to the general and comparative category of mysticism, but with light hands, so to speak. Above all, the papers all assume, if it may be put that way, a mysticality, a sense by which we can grasp something of what mystics say, even though those experiences might be ineffable and we do not (or cannot) have immediate access to what mystics claim. It is with this post-critique approach to mysticism that this Reprint seeks to contribute to the field and encourage further studies.